Common Fixed Point Results on b-Metric Spaces for Generalized Rational Type ϑ,ψ,φ-Weakly Contractive Mappings With Applications - Albray Gebremariam Kalo; Kidane Koyas Tola; Haider Ebrahim Yesuf (Abstract and Applied Analysis)
This paper focuses on existence and uniqueness of common fixed points for a pair of self-mapping satisfying generalized rational type ϑ,ψ,φ-weak contractive condition in which one of the mapping is α-admissible with respect to the other and weakly compatible mappings in the framework of b-metric spaces. The results presented herein generalize and improve some well-known results in the existing literature. Furthermore, we draw some corollaries from our results and provide an example for illustrating the validity of our findings. As an application of our result, we discuss the existence of a solution to a fractional order differential equation.